2022
DOI: 10.1063/5.0066153
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional roles of hairs and spines in old man of the Andes cactus: Droplet distant coalescence and mechanical strength

Abstract: Cactaceae have adapted to harsh environments by resisting intense solar radiation, retaining and collecting water. Some cacti species have hairs on them along with distinctive spines to serve different functions. In this study, we characterized the Old Man of Andes cactus (Oreocereus trolli). We examined the surface morphology and estimated roughness and adhesion force of both spines and hairs. They both consist of longitudinal microgrooves. The condensation experiments carried out on spines showed that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…An additional, speculative hypothesis is that hooks condense a higher quantity of atmospheric moisture in fog zones that then drips to the soil surface, increasing available water (Anderson, 2001 ). Recent research (Kundanati et al, 2022 ) found that the straight spines of the cactus Oreocereus trolli Kupper, which occurs in the fog deserts of the Andes in Argentina and Bolivia, channel a significant volume of water that coalesces first as dew. Future research on hooked spines facilitating increased available water for the root zone would be particularly relevant for Baja California Cochemiea , as several areas of diversity along the Pacific coast into the central desert feature regular fogs (Webb and Turner, 2015 ), and the often‐foggy Pacific Coast of Baja California is shown in our biogeographical reconstruction to be an important ancestral area (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional, speculative hypothesis is that hooks condense a higher quantity of atmospheric moisture in fog zones that then drips to the soil surface, increasing available water (Anderson, 2001 ). Recent research (Kundanati et al, 2022 ) found that the straight spines of the cactus Oreocereus trolli Kupper, which occurs in the fog deserts of the Andes in Argentina and Bolivia, channel a significant volume of water that coalesces first as dew. Future research on hooked spines facilitating increased available water for the root zone would be particularly relevant for Baja California Cochemiea , as several areas of diversity along the Pacific coast into the central desert feature regular fogs (Webb and Turner, 2015 ), and the often‐foggy Pacific Coast of Baja California is shown in our biogeographical reconstruction to be an important ancestral area (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hydrophilic surfaces structured with microgrooves exploit the flow of small droplets into larger ones through waterfilled grooves to improve the drainage of dew collected from the atmosphere. 15,16 Superhydrophobic surfaces provide an alternative as they drain dew through CICDJ and simultaneously possess self-cleaning properties. 17 CICDJ also enhances heat transfer by condensation thanks to the continuous droplet shedding and renucleation of small droplets.…”
Section: Introductionmentioning
confidence: 99%
“…While for some surfaces of plants , and insects CICDJ contributes to self-cleaning from pathogens and inert particles, in the academic and industrial fields it is studied for several applications. For example, hydrophilic surfaces structured with microgrooves exploit the flow of small droplets into larger ones through water-filled grooves to improve the drainage of dew collected from the atmosphere. , Superhydrophobic surfaces provide an alternative as they drain dew through CICDJ and simultaneously possess self-cleaning properties . CICDJ also enhances heat transfer by condensation thanks to the continuous droplet shedding and renucleation of small droplets. , For these reasons, in frosting conditions, it also provides a passive antifrost effect. , At negative temperatures, frost is often preceded by condensation .…”
Section: Introductionmentioning
confidence: 99%
“…Many drought-avoiding succulent plants (for review see Ogburn &Edwards, 2010 andMales, 2017) occur in habitats with extremely low soil moisture yet with periodically high air humidity due to a strong oceanic influence that results in fog and/or dew formation, such as the Atacama desert and the Baja California desert (part of the Sonoran Desert) in the Americas (Rundel et al, 1991;Webb & Turner, 2015), and the Succulent Karoo in southern Africa (Desmet & Cowling, 1999;Matimati et al, 2010). Indeed, fog-harvesting strategies and fog drip have been widely reported among succulents (Kundanati et al, 2022;Martorell & Ezcurra, 2002;Matimati et al, 2013;Mooney et al, 1977Mooney et al, , 1980Schulz et al, 2011), and water uptake by aerial parts has often been suggested. In the Americas, stem water uptake through the areoles has been long suspected in many Cactaceae (Barthlott & Capesius, 1974;Porembski, 1994;Schill & Barthlott, 1973), likely facilitated by fog-harvesting properties of spines and trichomes (Ju et al, 2012;Kim et al, 2017;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%